Unraveling hydrogeochemical dynamics and mixing mechanisms in North Shandong coastal aquifers: insights from isotopic and geochemical tracers - Liu, Zhenlin; Gao, Maosheng; Wang, Liangqing; Sun, Qiming; Chang, Xinyue; Hou, Guohua; Wang, Mengyao (Frontiers in Marine Science, 2025)
The muddy coastal region of North Shandong, China, including Laizhou Bay and the Huanghe River (Yellow River) Delta, is a complex depositional environment where land and sea intersect, creating diverse water types and intricate coastal groundwater formation and evolution. This study focuses on the shallow Holocene aquifer (SHA) and the deep Pleistocene aquifer (DPA) groundwater, using hydrogeochemical, isotope analysis and numerical simulation methods to infer the source of water and salt and hydrogeological chemical processes. The results reveal that the groundwater is a mix of seawater, freshwater, and brine, with significant differences in hydrochemical types and isotopic signatures between the SHA and DPA aquifers. The SHA groundwater is dominated by low salinity (TDS ≈ 8 g/L), with the freshwater dominated by Cl-Na and Cl-Na·Mg hydrochemical types. In contrast, the DPA groundwater is characterised primarily by high salinity (TDS ≈ 72 g/L) and the Cl-Na type. δ18O-δ2H deviates from the precipitation line and is close to the seawater evaporation line, indicating stronger seawater intrusion and salt accumulation processes. Interestingly, δ18O and δ2H stable isotopes' relative abundance in the DPA brine samples from the Huanghe River Delta (at a burial depth of 260 m) and Huanghe River water samples bear a resemblance, suggesting a strong correlation between the river water and the subsurface brine water source in the EPA. The Hydrochemical Facies Evolution Diagram (HFE–Diagram) analysis shows 63.77% of SHA samples underwent desalination, while 79.31% of DPA samples experienced seawater intrusion, this was restricted by structural constraints and rock salt dissolution. This study provides new insights into the hydrogeochemical evolution of coastal aquifers.